2008
DOI: 10.1007/s11060-007-9515-z
|View full text |Cite
|
Sign up to set email alerts
|

Single session stereotactic radiosurgery boost to the post-operative site in lieu of whole brain radiation in metastatic brain disease

Abstract: The use of SRS to the surgical site results in local recurrence rates comparable to WBXRT and is associated with excellent survival. Over 70% of patients managed this way were spared WBXRT. The presence of multiple lesions on presentation is predictive of the need for subsequent salvage WBXRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…17 We demonstrated a local recurrence rate of 6.25%, which was equivalent to the recurrence rate achieved with WBRT. The median survival was 16.4 months, and 72% of our patients were spared WBRT.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…17 We demonstrated a local recurrence rate of 6.25%, which was equivalent to the recurrence rate achieved with WBRT. The median survival was 16.4 months, and 72% of our patients were spared WBRT.…”
supporting
confidence: 57%
“…17 The rationale for adjuvant SRS to the operative bed is to maintain the local control benefits of radiation and surgery without introducing the risks of acute and chronic morbidities associated with WBRT. Our observed local recurrence rate of 7.7% compares favorably with published local failure rates at the surgical site following WBRT (range 10-20%) and is superior to the 46% failure rate reported for resection alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O'Neill and colleagues have shown that SRS is more effective at preventing local recurrences (0 %, 0/26) than surgery (27 %, 19/74). 46 In terms of surgery and SRS used together, a retrospective study has shown that giving a local boost of SRS into the surgical tumor bed has been shown to confer excellent survival and local control rates comparable to WBRT, sparing the patient the neurologic side effects of WBRT [47]. While SRS has been shown to be just as effective as surgery regarding survival, the inherent limitations of the retrospective analyses preclude the establishment of standard guidelines when comparing the two modalities; clearly, data from clinical trials can help resolve any controversy.…”
Section: Surgery and Stereotactic Radiosurgerymentioning
confidence: 99%
“…Among such options are post-op SRS 4,15,18,[23][24][25]27,28,30,31,35,39,48,50,55 and intraoperative application of either permanent low-dose 7,12,22,52 or temporary highdose 5,40,44,51,61 radio-isotopes (generally Iodine-125 (I-125)) into the surgical cavity. Postop SRS is the more commonly used of these treatment modalities due to its wider availability.…”
Section: Introductionmentioning
confidence: 99%